Antibacterial Activity of Extracts of Wild Mango (Mangifera spp.), Ruellia tuberosa L and Leucobryum sp. Causes of Gangrene in Patients with Diabetes Mellitus - Rodesia Mustika Roza; Fitmawati; Hari Kapli; Fitra Suzanti (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
Plants are the main medicinal source that exists around the world, due to the content of bioactive compounds such as flavonoids, alkaloids, saponins, polyphenols, tannins, terpenoids, and essential oils. These bioactive compounds have antimicrobial activity. The purpose of this study was to analyze the antibacterial activity of a combination extracts of Sumatran wild mango (M. sumatrana, and M. foetida var. Batu), R. tuberosa L. and Leucobryum sp. against bacteria that cause gangrene wounds in diabetics. Preparation of plant extraction is carried out by the method of maceration using 70% alcohol. Testing of antibacterial activity using the disc paper method 6 mm in diameter at an extract concentration of 10% with seven treatments (P1-P7). The test results obtained the largest inhibitory zone diameter against Staphyococcus aureus ATCC 6538 and S. epidermidis ATCC 12228 both shown in combination II extracts at P7 treatment (2:3:1 ratio), 9.04±1.42 mm and 8.85±0.21 mm, respectively. The results of the inhibitory zone resulting from the combination extract test included criteria of resistance to Staphylococcus. In the positive control, the diameter of the chloramphenicol inhibition zone against S. aureus belongs to the sensitive category, but to S. epidermidis it belongs to the resistant category. Combination of methanol extract from wild mango, R. tuberosa L and Leucobryum sp. has the opportunity as the candidate for natural-based antibiotics to replace synthetic antibiotics.